Therapeutic role of methanolic extract of pomegranate flower on tissues of albino rats dosed with cadmium sulphide nanoparticles - F. J. Al-Obaidi; R. M. Rashied; R. A. Jasim; M. S. AlRawi; A. Ramizy; A. F. Almehemdi (Regulatory Mechanisms in Biosystems, 2025)
Cadmium (Cd) is a hazardous toxin to human s and a major source of pollution in industrial and environmental fields. Compared with cadmium sulfide (CdS), cadmium is more toxic. Pomegranate plants are known for their antioxidant properties and potential medicinal uses due to their high levels of phenols and other compounds. This study was co n ducted to confirm the therapeutic activity of pomegranate flowers against cadmium sulfide poisoning. White rats were used as experimental subjects by analyzing tissue sections from multiple organs of animals after treatment with metabolite extracts of pomegranate flowers and organs of untreated animals . Pomegranate flowers were collected from several loc a tions, and the methanolic preparations were analyzed using gas chromatography with electron impact mass spectrometry (GC-MS). Electron microscopy was used to evaluate the physical properties of the laboratory-generated nano-cadmium sulfide solution. Five groups of white rats were assigned to the experiment. These groups were given 0 .00 , 0.025, 0.05 and 0.1 0 mg extract / kg + 0.1 μg CdS / m L , and just 0.1 μg CdS / m L . T hese treatments were applied. intraperitoneally Nano- cadmium sulfide doses were administered to the rat s regularly. R ats were given concentrated extract of pomegranate flower after 30 days. Three days later, the rats were dissected, and the organs – liver, kidney, spleen and heart – were taken out for laboratory analysis. The study concluded that methanol extracts of pomegranate flowers reduce d tissue toxicity, especially at high doses of 0.05 and 0.1 mg extract / k g . The heart responded better to this treatment than other studied organ tissues. Therefore, n anotoxicity of nano-cadmium sulfide w as significantly reduced in albino rat s by methanolic extract of pomegranate flowers.